PERAN PERCEIVED VALUE MEMEDIASI HUBUNGAN KUALITAS PELAYANAN DENGAN KEPERCAYAAN KONSUMEN - Suseno, Yenna Kurnia; Rahyuda, Ketut (E-Jurnal Manajemen; Vol 8 No 4 (2019)DO - 10.24843/EJMUNUD.2019.v08.i04.p11, 2019)
The purpose of this study was to explain the effect of service quality on consumer perceived value and trust in Puri Saron Hotel, to explain the effect of perceived value on consumer trust in Puri Saron Hotel, and to explain the role of perceived value mediating the relationship of service quality with consumer trust in Puri Saron Hotel. The sample determination technique in this study uses purposive sampling technique, which is a sample determination technique with certain considerations consisting of foreign tourists who are at least 20 years old and have stayed at Puri Saron Hotel at least once, with a sample size of 100 respondents. The analysis technique used in this study is by using path analysis techniques. Based on the results of the study showed that: 1) Service quality has a positive and significant effect on perceived value at Puri Saron Hotel, 2) Service quality has a positive and significant effect on consumer confidence in Puri Saron Hotel, 3) Perceived value has a positive and significant effect on consumer confidence in Puri Saron Hotel, and 4) Perceived value positively and significantly mediates the influence of service quality on consumer trust. Keywords: service quality, perceived value, consumer trust